Review on Multi Level Inverter Topologies and Control Strategies for Solar Power Conversion - Shivaleelavathi, B. G.; Srikanth, Chinmayi; Yatnalli, Veeramma (EMITTER International Journal of Engineering Technology, 2020)
Nowadays solar power has become an alternate method of power generation for standalone systems for both urban and rural electrification. The Power Electronics converters used for the power conversion should provide quality AC output to have near sinusoidal voltage. The inverter topology and the PWM technique of the inverter play a vital role in providing quality output. This paper reviews recent contribution to establish the current status and development of the technology to provide reader with an insightful review of multilevel inverters and its control strategy. A brief overview of Multi Level Inverters (MLI) topology and advantages of Cascaded H-Bridge Multi Level Inverter (CHBMLI) for solar power conversion is presented and the various control strategies for CHBMLI are discussed with view point of quality output. Among the different PWM techniques discussed, the Elliptical Multi Carrier PWM (EMC PWM) control strategy is the new modulation technique which successfully improves the DC bus utilization without over-modulation and without adding third harmonic to fundamental frequency. Also, the technique is successful in reducing the %THD at the output voltage. The control strategy is simple even with increased level of output voltage, which is not possible in SVPWM technique. Hence, the EMC PWM technique is having better performance when compared to Multi Carrier PWM (MCPWM) technique, Space Vector PWM (SVPWM) technique and Third Harmonic Injection PWM (THIPWM) technique.